Advances in cardioprotective strategies: Bridging traditional pharmacotherapy and regenerative medicine - Hladkykh Fedir V.; Matvieienko Mariia M.; Liadova Tetiana I; Karafulidi Olha V.; Komorovsky Roman R. (Scripta Medica, 2025)
Cardiovascular diseases (CVDs) remain the leading global cause of death and disability, underscoring the need for improved therapies. Key emerging strategies include pharmacological cardioprotection, cell-based therapies and the use of exosomes as therapeutic agents and biomarkers. Aim of this study was to characterise contemporary approaches to cardioprotection in CVDs, including pharmacological agents, cell-based therapies and exosome-based strategies, based on an analysis of evidence-based data. A systematic literature search was performed using databases including PubMed, Clinical Key (Elsevier), Cochrane Library, eBook Business Collection and Google Scholar. Keywords included cardioprotection, exosomes, cell-based therapies and pharmacological approaches. Article selection followed evidence-based medicine principles and the PRISMA guidelines. Current cardioprotective strategies include both traditional pharmacological agents, such as b-blockers, calcium channel blockers, ACE inhibitors, statins and nitrates, as well as innovative approaches like cell-based therapies and the use of exosomes. The advantages and limitations of cell therapy were analysed, including challenges related to low cell survival, failure of differentiation and the risk of arrhythmias. The role of exosomes and microvesicles as promising markers of cardiovascular injury and potential therapeutic agents was also explored. Combining pharmacological, cell-based and exosome-based strategies offers new prospects for cardioprotection in CVDs. Further research is required to optimise the clinical use of cell therapies and to confirm the efficacy of exosome-based interventions.